EPIDEMIOLOGICAL SITUATION OF BURNS IN SOME SPECIALIZED UNITS OF BRAZIL: INTEGRATIVE REVIEW (CIPEEX, 2022)
ABSTRACT&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP; &NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;&NBSP;BURNS ARE TRAUMATIC INJURIES THAT CAN BE CAUSED BY THERMAL, CHEMICAL, PHYSICAL, BIOLOGICAL, RADIOACTIVE OR ELECTRICAL AGENTS. IN BRAZIL, CASES OF BURNS REACH 1 MILLION PER YEAR, MOST OF WHICH OCCUR IN DOMESTIC ENVIRONMENTS. SERIOUS CASES WITH BURNS CAN LEAD TO HEMODYNAMIC INSTABILITY, IN ADDITION TO OTHER COMPLICATIONS SUCH AS RESPIRATORY, RENAL AND COAGULATION DISORDERS. THE OBJECTIVE OF THIS STUDY WAS TO DESCRIBE THE EPIDEMIOLOGICAL SITUATION OF BURNS IN SOME HOSPITALS IN BRAZIL, THROUGH AN INTEGRATIVE REVIEW OF REFERENCES THAT PRESENTED STATISTICAL ANALYZES ON BURNS. WE SELECTED 8 ARTICLES, 1 PUBLICATION OF THE MINISTRY OF HEALTH AND 2 BOOKS REFERENCES IN THE SUBJECT, USED TO PRESENT THE EPIDEMIOLOGICAL CHARACTERISTICS OF THE VICTIM POPULATION OF BURNS. RAPID PRE-READING OF THE CONTENTS OCCURRED, FOLLOWED BY ATTENTIVE AND REFLECTIVE READING, MAKING POSSIBLE SYNTHESES THAT HIGHLIGHTED THE PREVALENT MALE GENDER IN HOSPITALIZATIONS FOR BURNS ORIGINATED FROM OPEN FLAME, OVERHEATED LIQUIDS AND ALCOHOL. WITH WOMEN, BURNS OCCURRED ESPECIALLY IN THE DOMESTIC ENVIRONMENT, FOLLOWED BY THE ATTEMPT OF SELF-EXTERMINATION AND VIOLENCE WITH THE USE OF DIRECT FLAME AND ALCOHOL. CHILDREN AND THE ELDERLY WERE CONSIDERED TO BE VULNERABLE AND FRAGILE TO BURN INJURIES, DUE TO IMPAIRED OR IMPAIRED MOBILITY AND LOW OR NO PERCEPTION OF THE RISKS OF ACCIDENTS, WITH THE MAIN AGENT BEING THE HOT LIQUID. IT SHOULD BE EMPHASIZED THAT BURNS SHOULD BE PERCEIVED AS LESIONS WITH POTENTIAL FOR AGGRAVATION, BESIDES CAUSING SUFFERING TO THE PATIENT AND SEVERE SEQUELAE. IT IS UNDERSTOOD THAT APPROPRIATE CARE MUST BE CARRIED OUT BY A MULTIPROFESSIONAL TEAM SO THAT THE RISKS OF COMPLICATIONS AND DEATH BY THIS AGGRAVATION ARE REDUCED.
Keywords: Burns; burn injury; Health promotion